Isolation of carbon monoxide dehydrogenase from Acetobacterium woodii and comparison of its properties with those of the Clostridium thermoaceticum enzyme. - Ragsdale, S W (1983)
An oxygen-labile carbon monoxide dehydrogenase was purified to at least 98% homogeneity from fructose-grown cells of Acetobacterium woodii. Gel filtration and electrophoresis experiments gave molecular weights of 480,000 and 153,000, respectively, of the active enzyme. The molecular weights for the subunits are 80,000 and 68,000; the subunits occur in equal proportion. The small subunit of the A. woodii enzyme differs in size from that of the Clostridium thermoaceticum enzyme; however, the large subunits are similar. The specific activity of the A. woodii enzyme, measured at 30 degrees C and pH 7.6, is 500 mumol of CO oxidized min-1 mg-1 with 20 mM methyl viologen as the electron acceptor. Analysis revealed (number per dimer) iron (9), acid-labile sulfide (12), nickel (1.4), and magnesium or zinc (1). This metal content is quite similar to that of the C. thermoaceticum enzyme (Ragsdale et al., J. Biol. Chem. 258:2364-2369, 1983). The nickel as well as the iron-sulfur clusters are redox-active, as was found for the C. thermoaceticum enzyme (Ragsdale et al., Biochem. Biophys. Res. Commun. 108:658-663, 1982). CO can reduce and CO2 can oxidize the iron-sulfur clusters. The enzyme is inhibited by cyanide, but CO2 in the presence of reduced methyl viologen or CO alone can reverse or prevent this inhibition. Several ferredoxins, flavodoxin, and rubredoxin and some artificial electron carriers were tested for their relative rates of reaction with the CO dehydrogenases from A. woodii, C. thermoaceticum, and Clostridium formicoaceticum. Rubredoxin was by far the most reactive acceptor and is proposed to be the primary natural electron carrier for the acetogenic CO dehydrogenases.